The age of empire 1875-1914 - Hobsbawm, Eric (London Abacus Books, 1994)
In this third volume of his four-volume history of the modern world, as it has been produced by the development and expansion of the West, Eric Hobsbawm combines vast erudition with a graceful prose style to re-create the epoch that laid the basis for the twentieth century. (3z(BThough written by a professional historian,(3y (BHobsbawm writes of his own work, (3z(B[it] is addressed not to other academics, but to all who wish to understand the world and who believe history is important for this purpose.s